Charity Donations and the Euro Introduction : Some Quasi-Experimental Evidence on Money Illusion - Peter Kooreman; Riemer Faber; Heleen Hofmans (Institute for the Study of Labor (IZA), 2004)
We compare the revenues of a house-to-house collection for a charity before and after the introduction of the euro in a ceteris paribus setting. We find strong evidence of money illusion, supplementing earlier econometric, experimental, and survey evidence on its existence.
Keywords: D12; 330; money illusion; quasi-experiment; behavioral economics; Geldillusion; Spende; Euro; Niederlande